Examination of trauma levels and earthquake stress coping strategies of university students who exercise and do not exercise after an earthquake - Zekai Çakır; Ülfet Erbaş; Mevlüt Gönen; Mehmet Ali Ceyhan; Tuncay Öktem; Murat Kul; Ahmet Naci Dilek; Sema Güzel (BMC Psychology)
Abstract Background Earthquakes are calamities of devastating nature that induce longterm post traumatic stress on affected victims. As such, they are recognized worldwide as being huge sources of stress. In this research study, the first objective is to assess the level of trauma and earthquake stress of university students who exercise and those who do not. Methods This study utilized the descriptive survey research method. The sample comprised 378 male and 300 female students who experienced the socially detrimental 7.7 Mw and 7.6 Mw earthquakes in Turkey on February 6, 2023. The data were both face-to-face and via computer-administered questionnaire with the tools of “Post-Earthquake Trauma Level Scale” and “Earthquake Stress Coping Strategies Scale.” After checking for normality, the parametric tests were used, the t-test to compare two groups of data, and ANOVA for three or more groups of data. Furthermore, Pearson correlation analyses were performed to compare the interactions between students who exercise and those who do not. Results The study found that gender affected trauma levels, with female students (X = 73.483) exhibiting significantly higher trauma levels than male students (X = 68.799) (p < 0.001). Students who engaged in regular physical activity (X = 67.71) were found to have lower trauma levels compared to those who did not exercise (X = 71.97). Participants who feared being caught by the earthquake at home or school (X = 73.32), experienced the loss of someone close (X = 88.10) or believed that adequate precautions against the earthquake had not been taken (X = 71.73) had higher trauma scores. According to the results of the ANOVA test, students from the Departments of Sports Sciences (X = 69.78) and Religious Studies (X = 69.63) were observed to have lower trauma levels. Pearson correlation analysis showed a positive and moderate relationship between trauma levels and earthquake stress coping strategies among students who engaged in regular physical activity (r = .176, p < 0.01). Conclusions The research identified that factors such as gender, regular exercise, the experience of losing a loved one, and the perception that insufficient precautions were taken all significantly influence trauma levels. Moreover, the findings highlighted that regular physical exercise serves as an effective strategy for managing and coping with trauma.